Deep Eutectic Solvents as Catalysts for Cyclic Carbonates Synthesis from CO2 and Epoxides - Dorota Mańka; Agnieszka Siewniak (Molecules, 2022)
In recent years, the chemical industry has put emphasis on designing or modifying chemical processes that would increasingly meet the requirements of the adopted proecological sustainable development strategy and the principles of green chemistry. The development of cyclic carbonate synthesis from CO2 and epoxides undoubtedly follows this trend. First, it represents a significant improvement over the older glycol phosgenation method. Second, it uses renewable and naturally abundant carbon dioxide as a raw material. Third, the process is most often solvent-free. However, due to the low reactivity of carbon dioxide, the process of synthesising cyclic carbonates requires the use of a catalyst. The efforts of researchers are mainly focused on the search for new, effective catalysts that will enable this reaction to be carried out under mild conditions with high efficiency and selectivity. Recently, deep eutectic solvents (DES) have become the subject of interest as potential effective, cheap, and biodegradable catalysts for this process. The work presents an up-to-date overview of the method of cyclic carbonate synthesis from CO2 and epoxides with the use of DES as catalysts.